2011
DOI: 10.1007/s00198-011-1749-0
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends of hip fractures in Québec, Canada

Abstract: Differences observed in hip fracture rates as well as in secular trends between age groups and gender emphasise the need for decision makers to rely on results based on age-specific and sex-specific analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Regional studies from Ontario and Quebec showed a similar trend in hip fracture rates as the national study, showing a plateau in the age-adjusted rates through the 1980s, followed by a progressive acceleration in the decline after the mid-1990s. (17)(18)(19)(20) A more recent large regional study from the province of Manitoba examined fractures in men and women aged 50 years and above between 1986 and 2006, (21) demonstrated annual declines in age-adjusted hip fracture rates of 1% in women and 0.7% in men, with an acceleration of the rate of decline after 1996 in both men and women comparable to the trend reported in the national and other regional studies.…”
Section: North Americasupporting
confidence: 55%
See 2 more Smart Citations
“…Regional studies from Ontario and Quebec showed a similar trend in hip fracture rates as the national study, showing a plateau in the age-adjusted rates through the 1980s, followed by a progressive acceleration in the decline after the mid-1990s. (17)(18)(19)(20) A more recent large regional study from the province of Manitoba examined fractures in men and women aged 50 years and above between 1986 and 2006, (21) demonstrated annual declines in age-adjusted hip fracture rates of 1% in women and 0.7% in men, with an acceleration of the rate of decline after 1996 in both men and women comparable to the trend reported in the national and other regional studies.…”
Section: North Americasupporting
confidence: 55%
“…The result is expressed in percent change/year. (11) 1972-1992 R(Rochester) -0.6 þ1.4 -0.2 Melton and colleagues (2009) (12) 1980-2006 R(Rochester) -1.4 -0.06 Brauer and colleagues (2009) (13) 1985-1995 N þ0.9 þ1.6 Brauer and colleagues (2009) (13) 1995 (21) 1986-2006 R(Manitoba) -1 -0.5 Vanasse and colleagues (2012) (20) 1993 (25) 1997-2006 N -2.2 -2 Rosengren and colleagues (2013) (26) 1993-2010 N -1.2 Finland Korhonen and colleagues (2013) (27) 1970-1997 N þ2.2 þ3.8 Korhonen and colleagues (2013) (27) 1997-2010 N -1.9 -1 Iceland Siggeirsdottir and colleagues (2014) (35) 1989-2000 N þ1.3 Siggeirsdottir and colleagues (2014) (35) 2000-2008 N -2.2 Siggeirsdottir and colleagues (2014) (35) 1989-2004 N þ2.7 Siggeirsdottir and colleagues (2014) (35) 2004-2008 N 0 Norway…”
Section: North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…But hip fracture incidence varies among countries [4,5]. During the past decade, hip fracture incidence has declined in most Western countries and Oceania [5][6][7][8][9][10][11][12][13][14], reached a plateau [15,16] and increased in some countries in Asia and South America [5,17]. In France, we previously showed that the incidence of hip fractures decreased in both genders from 2002 to 2008 [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, healthy elderly individuals are particularly prone to catastrophic events at any moment of their lives. One stressful event for individuals aged 65 and older is a fall that results in a fracture of the hip (HF) [3,4]. HF can have serious outcomes such as chronic pain, disability, high morbidity, susceptibility to major depression, loss of autonomy in individuals who were generally autonomous before the event and, frequently, institutionalization.…”
Section: Introductionmentioning
confidence: 99%